The Students’ Readiness in Facing Offline Class After Pandemic Covid-19 at The Eleventh Grade Students’ of UPT SMAN 4 Parepare - HS, Tri Mulyanugrahah; Salasiah, Salasiah; Sakti, Ika Yanti (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2022)
The COVID-19 virus in Indonesia is currently having an impact on the entire community and has an impact in various fields such as social, economic, religious fields, including the field of education. In the field of education, the government has set one policy, namely online schools as a solution during the current pandemic. This study was conducted to determine how prepared students are to face offline classes after the COVID-19 pandemic. This research used desciptive qualitative approach and the data analysis Braun and Clarke. Participants in this study were 11th grade students of SMAN 4 Parepare which consisted of 15 students. The data in this study were obtained using semi-structured interviews and chosing random samplin. From the results of the study, it is known that the students are ready for offline learning to be held at school. They are ready if given an uncertain study schedule, facing new media and different learning methods during offline learning. Most importantly, students will also continue to apply health protocols during offline learning. In addition, the students were also enthusiastic about the resumption of offline learning because they found it difficult to understand the material given by their teacher during online learning, and because they met again with their teacher and classmates.